2015
DOI: 10.1021/acs.langmuir.5b02273
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Recognition by a Tubular Assembly of Phenylene–Pyrimidinylene Alternated Macrocycle through Hydrogen-Bonding Interactions

Abstract: Study of artificial tubular assemblies as a useful host scaffold for size-selective recognition and release of guest molecules is an important subject in host-guest chemistry. We describe well-defined self-assembled nanotubes (NT6mer) formed from π-conjugated m-phenylene-pyrimidinylene alternated macrocycle 16mer that exhibit size-selective recognition toward a specific aromatic acid. In a series of guest molecules, a size-matched trimesic acid (G3) gives inclusion complexes (NT6mer⊃G3) in dichloromethane resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The host molecule 1 6mer is a shape-persistent macrocycle with a large macrocyclic cavity and rich flexible long alkoxy side chains; these features make it an attractive candidate for constructing a stable host template with a nanoporous configuration that can be further used to host a variety of guest molecules. As previously reported, 2D porous networks self-assembled by 1 6mer were successfully obtained on the solid surface. , In this paper, we demonstrated the construction of an exquisite three-component co-assembly structure (1 6mer –COR–C 60 ) by adding COR and C 60 guest molecules into the 1 6mer host template. Through STM observations and DFT calculations, we found that the adding sequence of the guest molecules on the base of the 1 6mer host template plays a decisive role in the generation of the 1 6mer –COR–C 60 structure.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The host molecule 1 6mer is a shape-persistent macrocycle with a large macrocyclic cavity and rich flexible long alkoxy side chains; these features make it an attractive candidate for constructing a stable host template with a nanoporous configuration that can be further used to host a variety of guest molecules. As previously reported, 2D porous networks self-assembled by 1 6mer were successfully obtained on the solid surface. , In this paper, we demonstrated the construction of an exquisite three-component co-assembly structure (1 6mer –COR–C 60 ) by adding COR and C 60 guest molecules into the 1 6mer host template. Through STM observations and DFT calculations, we found that the adding sequence of the guest molecules on the base of the 1 6mer host template plays a decisive role in the generation of the 1 6mer –COR–C 60 structure.…”
Section: Introductionsupporting
confidence: 63%
“…CHCl 3 , tetrahydrofuran (THF), trifluoroacetic acid (TFA), and 1-phenyloctane solvents were purchased from Aldrich. The 1 6mer host molecule was prepared according to previously reported procedures. , Coronene (COR) and C 60 fullerene guest molecules were purchased from Acros (chemical structures are shown in Scheme ). The solutions for the STM experiment were obtained by dissolving the host or guest molecule in a specific solvent.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we have reported that macrocycle 1 could self-assemble into welldefined nanotubes via p-p interactions in dichloromethane, which showed precision size-selective recognition toward trimesic acid (TMA) and formed an inclusion complex through hydrogenbonding interactions. 4 In the present work, we described that selfassemblies based on the pyrimidinylene-phenylene macrocyclic skeleton could interact with strong acids by protonation in the solution, which caused the disassembly or transformation of the self-assemblies through electrostatic repulsions and changes in planarity of macrocyclic backbones. Their morphologies were tuned back to the original state through simple deprotonation by addition of a base into the solution to recover p-p forces.…”
mentioning
confidence: 82%
“…These changes were quite different from the phenomena in the previous work that the broad aromatic peaks of 1 NT remained and the proton signal of the pyrimidine ring disappeared with increasing addition of TMA. 4 On the other hand, fluorescence spectral changes were not observed when CF 3 COOCH 2 CH 3 , an esterification product of TFA, was added into the CH 2 Cl 2 solution of 1 NT (Fig. S2, ESI †).…”
mentioning
confidence: 99%
See 1 more Smart Citation